2021
DOI: 10.1080/26895269.2021.1884925
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of trans and gender diverse young people accessing primary care and gender-affirming medical services: Findings from Trans Pathways

Abstract: Background: Increasing numbers of trans young people are seeking medical services worldwide, but there have been few qualitative investigations of the experiences of trans young people attempting to engage with these services to explore in-depth experiences of clinical interactions. Aims: We aimed to explore the experiences of trans young people accessing primary care and gender-affirming medical services in Australia for reasons related to their gender. Methods: Using data from a large mixed methods cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
2
39
1
Order By: Relevance
“…2018; Strauss et al. 2021), lack of access due to geographic location (Nemoto et al. 2015; White Hughto et al.…”
Section: Discussionmentioning
confidence: 99%
“…2018; Strauss et al. 2021), lack of access due to geographic location (Nemoto et al. 2015; White Hughto et al.…”
Section: Discussionmentioning
confidence: 99%
“… 111 It is well documented that trans people face disproportionate barriers to accessing health care compared with cis people. 112 114 Since it is currently not commonplace for medical practitioners to receive training on trans health, many clinicians are often uninformed of a trans person’s specific needs and unable to provide appropriate recommendations for their care. 115 As a result, trans people are more likely to delay seeking medical attention, resulting in increased morbidity from poor asthma control, for example.…”
Section: Translation Of Immunological Impact Of Sex Hormonesmentioning
confidence: 99%
“… 148 Trans people have often experienced discrimination, stigma and health care provider ignorance in previous attempts to access medical care, which often results in hesitancy to seek out medical attention, which delays treatment. 114 These barriers have been reported to result in less frequent HIV/STI testing. 115 In an Australian national survey of sexual health clinics, it was found that the incidence of HIV was around 3.5% in trans males and 5.7% in trans females on first visit, which is significantly higher than 1.2% in cis individuals.…”
Section: Translation Of Immunological Impact Of Sex Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of healthcare services is mainly influenced by urban and rural systems, as well as economic, social, ethnic, occupational, and gender factors [38][39][40]. With the combination of these multiple influences, building equity in healthcare services in a region will be a long and slow process of change [41].…”
Section: Covid-19 Exacerbates Inequities In Healthcare Accessibilitymentioning
confidence: 99%